Commodification of Ponan Tradition Myth as Tourism Promotion Based on Samawa Tribe's Local Wisdom - Gunawan, Hendra; Diana, Jumianti (Universitas Syiah Kuala, 2024)
The existence of myths in the ponan tradition according to the Samawa community is very important and sacred. In addition to being a tradition passed down from generation to generation, the myth of the ponan tradition is also a tourist destination that is always crowded with tourists not only from the local community, but also visitors or tourists from various countries. The purpose of this research is to describe the transformation of the mythical ritual of the ponan tradition which is considered sacred and can be a tourist attraction, as well as mapping the character of visitors to find out how much influence the myth of the ponan tradition can affect visitor interest. The method in this research uses a descriptive qualitative approach. The method in this research has five main stages, namely literature study, research implementation, data analysis of research results, providing conclusions and suggestions, and compiling reports and dissemination of research results. Data collection methods in this study include observation, interviews, and documents. The data analysis technique used in this research is interactive analysis.In the rituals of the ponan tradition, there are several myths that develop, namely the pilgrimage to the grave of H. Batu and pasaji ponan. In addition, there are cultural activities and folk entertainment, in the form of ratib rabanna ode, sakeco, lawas, and trif tours around Sumbawa. In essence, the activities that occur in it have automatically been commodified as added value that has an impact on the economic growth of the surrounding community, especially tourism actors. In the celebration of the ponan tradition, several types of visitors were also found, including pilgiaris and generalais visitors. These two types of visitors are evidence that in the ponan tradition there are visitors who come with special intentions, such as wanting to get blessings, have their affairs expedited, and avoid disasters. This type of visitor is called the pilgiaris type of visitor, then in the generalist type, visitors only come to enjoy entertainment, and vacation to fill empty time. This type of generalist visitor has no specific purpose and knowledge related to the ponan tradition.